Principles of modern chemistry / David W Oxtoby; H P Gillis; Alan Campion - Oxtoby, David W
Suitable for honors and high-level mainstream general chemistry courses, this text focuses on important key objectives, equations and concepts, and presents various applications to a wide range of disciplines, such as biology, chemical engineering, biochemistry, and medicine that deepen students' understanding of the relevance of chemistry.